Social policy and labour supply: The impact of activating labour market institutions on reservation wages - Fuchs, Benjamin; Prechsl, Sebastian; Wolbring, Tobias (Socio-Economic Review, 2023)
Activation is an efficacious policy paradigm in modern welfare states. Taking the case of Germany, we study the relationship between the embeddedness of benefit recipients in activating labor market institutions and individual labor supply. Using panel data, we estimate the effects of transitions between key institutional states with different degrees of activation on reservation wages. We show that reservation wages react to activation: the transition from gainful employment to unemployment benefit receipt leads to an average decrease of 3.1 percent in reservation wages. The transition from gainful employment to welfare benefit receipt – an institutional state with far more rigorous activation – leads to a stronger decrease of 4.9 percent. Mediation analyses show that the income associated with different institutional states is the predominant mechanism that drives the effect on reservation wages. However, subjective social status also partly mediates the effect. Implications of these findings for active labor market policies are discussed. <
Keywords: Labor market institutions; labor supply; social policy; social security; wages; welfare state; Gender